2021
DOI: 10.3390/ma14061441
|View full text |Cite
|
Sign up to set email alerts
|

Jumping Wave Characteristic during Low Plasticity Burnishing Process

Abstract: During the low plasticity burnishing process of soft materials such as carbon steel with a hardness of up to 40 HRC (Rockwell grade) a raised structure of the material known as the Jumping Wave forms in front of the tool roll. This phenomenon significantly disturbs the burnishing process, but is very poorly described in the literature. This article presents studies of this phenomenon on the example of burnished 1.0562 steel. The research concerns the changes in the surface structure of the processed material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Movement of the roller in relation to the material, which is a combination of burnishing speed and feed motion, causes most of the flowing material to accumulate in front of the tool. The creation of an additional material structure in front of the tool is noted in the literature and in workshop slang is referred to as the “jumping wave” [ 36 , 37 ] or “the wave of plastically deformed material” [ 22 ]. The equivalent plastic strain values in the zone of the “jumping wave” have much higher values (point B in Figure 21 a) than in the stable burnishing zone.…”
Section: Resultsmentioning
confidence: 99%
“…Movement of the roller in relation to the material, which is a combination of burnishing speed and feed motion, causes most of the flowing material to accumulate in front of the tool. The creation of an additional material structure in front of the tool is noted in the literature and in workshop slang is referred to as the “jumping wave” [ 36 , 37 ] or “the wave of plastically deformed material” [ 22 ]. The equivalent plastic strain values in the zone of the “jumping wave” have much higher values (point B in Figure 21 a) than in the stable burnishing zone.…”
Section: Resultsmentioning
confidence: 99%
“…To minimize the surface roughness, the rolling speed, pressure, and the number of passes should be set at high levels; on the contrary, the ball diameter should be at a low level, because of a strong interplay between rolling speed and ball diameter. In addition, Dzionk et al [ 69 ] investigated the jumping‐wave (raised structure) characteristics of a type of carbon steel during LPB when the hardness was strengthened up to 40 HRC. They found that jumping waves formed in the front of the LPB tool, thereby significantly affecting the stability of the burnishing process.…”
Section: Influence Of Lpb On Mechanical Performancementioning
confidence: 99%